EFEKTIVITAS PEMBELAJARAN FIGH BERBASIS PROJECT-BASED LEARNING DALAM MENGEMBANGKAN KREATIVITAS SISWA MAN BANGKALAN - Mohammad Ali Wafa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to improve the effectiveness of Fiqh learning and develop students’ creativity through the implementation of the Project-Based Learning (PjBL) method at MAN Bangkalan. The PjBL approach provides a contextual, project-oriented learning experience and encourages students to be active and creative in solving problems. This study employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, acting, observing, and reflecting stages. The subjects of this study were 30 students of MAN Bangkalan. Data were collected through observation, interviews, documentation, and assessment of students’ work. Data analysis was carried out descriptively, both qualitatively and quantitatively, to assess the increase in students’ creativity and learning effectiveness. The results showed that the implementation of Project-Based Learning significantly improved the effectiveness of Fiqh learning and students’ creativity. In the first cycle, the level of students’ creativity was in the fair category (averaging 65%), while in the second cycle, it increased to the good category (averaging 85%). Furthermore, students’ participation in the learning process also increased, as evidenced by their active involvement in group discussions, project presentations, and the completion of creative tasks. This study concludes that the PjBL method is effective in enhancing students’ creativity and making Fiqh learning more engaging, contextual, and relevant to everyday life. The researcher recommends the use of the PjBL method as an alternative approach to Fiqh learning in madrasahs.